2020
DOI: 10.1212/wnl.0000000000008981
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flavonols and risk of Alzheimer dementia

Abstract: ObjectiveTo determine whether dietary intake of flavonols is associated with Alzheimer dementia.MethodsThe study was conducted among 921 participants of the Rush Memory and Aging Project (MAP), an ongoing community-based, prospective cohort. Participants completed annual neurologic evaluations and dietary assessments using a validated food frequency questionnaire.ResultsAmong 921 MAP participants who initially had no dementia in the analyzed sample, 220 developed Alzheimer dementia. The mean age of the sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 29 publications
4
99
0
1
Order By: Relevance
“…Improvements in resting regional cerebral blood flow have also been reported following an acute ingestion of high-flavanol (494 mg) cocoa drink [30] and after daily ingestion of 387 mg anthocyanin-rich blueberry concentrate for 12 weeks [31]. More interestingly, an ongoing (1997-present) community-based, prospective cohort of 921 older persons showed that higher dietary intakes of flavanols may be associated with reduced risk of developing Alzheimer dementia [34]. However, other studies have reported nonsignificant effects or even unwanted effects of (poly)phenol-rich supplementation on certain cognitive functions, specifically executive functioning, working memory and verbal memory [35,36], or cerebral blood flow response [37].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Improvements in resting regional cerebral blood flow have also been reported following an acute ingestion of high-flavanol (494 mg) cocoa drink [30] and after daily ingestion of 387 mg anthocyanin-rich blueberry concentrate for 12 weeks [31]. More interestingly, an ongoing (1997-present) community-based, prospective cohort of 921 older persons showed that higher dietary intakes of flavanols may be associated with reduced risk of developing Alzheimer dementia [34]. However, other studies have reported nonsignificant effects or even unwanted effects of (poly)phenol-rich supplementation on certain cognitive functions, specifically executive functioning, working memory and verbal memory [35,36], or cerebral blood flow response [37].…”
Section: Introductionmentioning
confidence: 88%
“…These (poly)phenol compounds (i.e., flavones, flavonols, isoflavones, flavanones/flavanonols, flavanols, and anthocyanidins) are present in high amounts in fruits, vegetables, and natural products such as parsley, celery, onions, leeks, broccoli, soy, oregano herbs, green tea, red wine, citrus fruit, berry fruits, and dark chocolate [20,21]. Although research has historically focused on antioxidant properties [22][23][24][25], recent data from randomized placebo-controlled trials suggest (poly)phenols may also modulate neurological disorders, cerebral hypoperfusion, and neuroinflammation while simultaneously enhancing memory, learning, and cognitive performances in old-aged adults [19,[26][27][28][29][30][31][32][33][34]. Mastroiacovo et al [26] demonstrated a daily consumption of 250 mL Cocoa drinks, with a high flavanol content (993 mg), for 8 weeks has the potential to improve psychomotor performance, verbal fluency performance, as well as the overall cognitive performance (i.e., z-score).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons are likely to be the short time of intervention and the smaller sample size. Furthermore, Kaempferol is a natural flavonol, a type of flavonoid that can up-regulate the satiety gene NUCB-2/ nesfatin-1, which plays an essential role in controlling energy balance, reducing body weight, and increasing satiety [13,[46][47][48]. Nesfatin-1 can produce several activities, including suppressing inflammation, lipid mobilization activity, enhancement of antioxidant defense, and a regulatory role in glucose homeostasis, which can prevent and decrease the complications, development, and progression of T2DM [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons are likely to be the short time of intervention and the lower sample size in the study. Furthermore, Kaempferol is a natural avonol, a type of avonoid that can up-regulate the satiety gene NUCB-2/nesfatin-1 which plays an important role in controlling energy balance, reducing body weight and increasing satiety (13,(45)(46)(47) . Nesfatin-1 can produce several activities including suppression of in ammation, lipid mobilization activity, enhancement of antioxidant defense, and a regulatory role in glucose homeostasis that may prevent and reduce the complications, development, and progression of T2DM (48)(49)(50) .…”
Section: Discussionmentioning
confidence: 99%